POSTPARTUM DEPRESSION AND ANXIETY: A COMMUNITY-BASED STUDY ON RISK FACTORS BEFORE, DURING AND AFTER PREGNANCY - ULLAH, I; JAVED, A; ARIF, M; MARYAM, .; HASEEB, M; AQIL, B; AFRASIYAB, M (Biological and Clinical Sciences Research Journal, 2023)
Postpartum anxiety and depression are a significant public health concern as it is the leading cause of maternal morbidity. It is associated with adverse effects on the cognitive and social development of the infant. The primary aim of the study is to find postpartum depression and anxiety as a community-based study on risk factors before, during, and after pregnancy. The prospective cohort study was conducted in Khyber Teaching Hospital Peshawar from April 2023 to July 2023. A total of 320 pregnant women were recruited for this study. Participants were enrolled during their antenatal visits to healthcare facilities within the community, ensuring representation across diverse demographic and socio-economic backgrounds. Data collection for this community-based study on postpartum depression and anxiety was executed meticulously across three distinct phases: before, during, and after pregnancy. Data was collected from 320 pregnant females. The mean age of participants was 28.5±4.2 years. Most participants had at least a high school education (65%) and reported a moderate household income (55%). 18% of participants had a history of previous episodes of depression or anxiety. 35% reported experiencing significant life stressors before pregnancy, with financial concerns being the most common (62%). 24% had a family history of mental health disorders. It is concluded that this study has revealed a significant prevalence of postpartum depression (22%) and anxiety (18%) among participants. The identified risk factors, including prior mental health history and high prenatal stress, emphasize the need for early intervention and targeted support systems during the perinatal period.